Establishing Uniform Headings for the Sacred Scriptures: A Persistent Issue in Hebraica-Judaica Cataloging - Suiter, David (Judaica Librarianship, 1995)
The Library of Congress headings used for the Bible are theologically laden terms showing a clear preference for Christian designations (Old Testament and New Testament). This is so despite the fact that four-fifths of what Christianity calls "Bible" is also scripture for Judaism (called Bible or Tanakh). This paper explores the issues in identifying sacred scriptures for catalog access. Several alternatives to the qualifiers O.T. and N.T. are posited, including one proposal to replace the terms altogether with First Testament and Second Testament. Such terminology would account for the canons of the distinct religious communities by replacing the theological terms with terms that are historically objective.